2012
DOI: 10.4161/pri.21250
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosylation of Cdk5

Abstract: A berrant activation of Cdk5 has been implicated in the process of neurodegenerative diseases such as Alzheimer disease (AD). We recently reported that S-nitrosylation of Cdk5 (forming SNOCdk5) at specific cysteine residues results in excessive activation of Cdk5, contributing to mitochondrial dysfunction, synaptic damage and neuronal cell death in models of AD. Furthermore, SNO-Cdk5 acts as a nascent S-nitrosylase, transnitrosylating the mitochondrial fission protein Drp1 and enhancing excessive mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…In the adult brain, Cdk5 is in close proximity to a membrane-bound protein complex containing nNOS/PSD-95/NMDAR. Cdk5 can form a complex with nNOS and become a target of S-nitrosylation under pathological conditions (Zhang et al, 2010; Qu et al, 2011; Qu et al, 2012). Indeed, SNO-Cdk5 is highly expressed in human AD postmortem brains but not in normal control brains (Qu et al, 2011).…”
Section: Oxidative and Nitrosative Stress In Alzheimer’s And Parkinsomentioning
confidence: 99%
“…In the adult brain, Cdk5 is in close proximity to a membrane-bound protein complex containing nNOS/PSD-95/NMDAR. Cdk5 can form a complex with nNOS and become a target of S-nitrosylation under pathological conditions (Zhang et al, 2010; Qu et al, 2011; Qu et al, 2012). Indeed, SNO-Cdk5 is highly expressed in human AD postmortem brains but not in normal control brains (Qu et al, 2011).…”
Section: Oxidative and Nitrosative Stress In Alzheimer’s And Parkinsomentioning
confidence: 99%
“…According to their biotin-switch data, it has shown that SNO-Drp1 levels are elevated in Cdk5-transfected cells, which cause massive mitochondrial fragmentation compared with control plasmid-transfected cells. These findings suggest that transnitrosylation of NO from Cdk5 to Drp1 might be involved in the pathway to SNO-Cdk5–mediated spine loss, and eventually results in neuronal cell death AD [192, 193]. …”
Section: Drp1 and Cdk5 In Alzheimer’s Diseasementioning
confidence: 99%
“…Thus, S-nitrosylated Cdk5 not only has higher kinase activity but also acts as a nascent transnitrosylase. Importantly, S-nitrosylation of Cdk5 is enhanced in the presence of Ab and N-methyl-D-aspartate (NMDA) (Qu et al, 2011;Qu et al, 2012), suggesting that deregulated Cdk5 also induces neurotoxicity through aberrant S-nitrosylation reactions under pathological conditions.…”
Section: S-nitrosylationmentioning
confidence: 99%